Optimasi Formula dan Evaluasi Sediaan Sabun Transparan dari Putik Saffron (Crocus Sativus L.) - Gita Dwi Puspa Fadillah; Gabena Indrayani Dalimunthe (Student Scientific Creativity Journal, 2023)
Transparent solid soap, namely soap in the form of a bar with a transparent appearance, the resulting foam on the skin is softer. Saffron has been used as a food ingredient, treatment, and traditional medicine since ancient times. The content of saffron is like saponins which can be used in making transparent soap. This study aims to formulate a transparent soap from saffron essence as a skin protecting property. This research includes the manufacture of saffron extract, manufacture of transparent soap and transparent soap test parameters including organoleptic test, pH test, foam stability test, water content test and preference test by respondents. Based on research results, saffron extract can be formulated into transparent solid soap preparations that meet the requirements for water content in accordance with SNI, namely for F0 9.12 ± 0.56, FI 8.6 ± 0.42, F2 8.6 ± 0.43, F3 8.6±0.93. For the results of the foam height test, it was found that the foam results were quite stable. For the results of the irritation test, it can be concluded that soap preparations containing saffron essence are safe to use because they do not show any side effects after use.